A Plate Type Edge-Lift Anchor: Panel Reinforcement Influence on Failure Loads - Barraclough, Andrew; Lloyd, Natalie (Engineers Australia, 2012)
Ultimate capacity information for lifting inserts, and its associated supplementary reinforcement, used in lifting concrete thin walled element are summarised in this paper. Based on recent research, the capacity of a lifting insert is influenced by the capability of supplementary reinforcement to distribute stresses when anchor loads are applied. This paper shows various reinforcement combinations and how they influence the ultimate capacities of plate style edgelift anchor. Tests were conducted in direct tension, total of 97 tests, and in a shear direction, total of 8 tests. The test results show that by using double N12 perimeter bars with a double layer SL82 mesh, compared against centrally placed SL82 shrinkage mesh and centrally placed N16 perimeter bar, the anchor capacity is increased, by a tensile ultimate anchor capacity of 25% at 20MPa, fcm, and a shear anchor ultimate load capacity increase of 20%. These tests show that a N16 perimeter bar and a N16 shear bar installed with a plate edgelift anchor, the tensile ultimate load is reduced on average by 20%, at 16MPa, when compared to the same reinforcement configuration without a shear bar.